Nurses in the world of politics and leadership — selection of biographies - Lass, Piotr; Gaworska-Krzemińska, Aleksandra (Nursing Problems / Problemy Pielęgniarstwa, 2012)
The authors present the biographies of 20 nurses and 1 male nurse, who were influential in politics: six of royal families, three prime-ministers, five one revolutionary person, also the popular lord-mayors and human and women rights activists. The above mentioned persons did not change too much world or their countries politics, (with two exemptions) they usually they helped to turn the course of their countries politics to more towards the more rational solutions. Additionally, usually they proved very efficient in leadership and administration and human rights activists. Problemy Pielęgniarstwa 2012; 20 (4): 506–511